2020
DOI: 10.2147/dmso.s279306
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Health-Related Quality of Life and Associated Factors Among Type Two Diabetic Patients on Follow-Up in Dessie Comprehensive Specialized Hospital, Dessie, North East Ethiopia, 2020</p>

Abstract: Background: Diabetes mellitus is a disorder of carbohydrate metabolism and it is highly related with diminished HRQOL in Ethiopia; diabetic related complications especially bring major negative impacts on HRQOL. Objective: To assess HRQOL and associated factors among type two diabetic patients in Dessie Comprehensive Specialized Hospital, north east Ethiopia, 2020. Methods: Institutional-based cross-sectional study design was conducted on 417 patients through systematic random sampling technique from February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Additionally, the findings illustrate that diabetes-related complications, old age, obesity, duration of diabetes, insulin and oral anti-diabetic medication use were the major predictors that require comprehensive intervention strategies to enhance the HRQoL of patients with diabetes. Furthermore, the findings showed that HRQoL remains the most disregarded component in routine clinical practice in Ethiopia [19,[30][31][32]. Hence, this study aimed to evaluate the HRQoL and associated factors among patients with T2DM at a tertiary teaching hospital in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the findings illustrate that diabetes-related complications, old age, obesity, duration of diabetes, insulin and oral anti-diabetic medication use were the major predictors that require comprehensive intervention strategies to enhance the HRQoL of patients with diabetes. Furthermore, the findings showed that HRQoL remains the most disregarded component in routine clinical practice in Ethiopia [19,[30][31][32]. Hence, this study aimed to evaluate the HRQoL and associated factors among patients with T2DM at a tertiary teaching hospital in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, improved QoL is regarded as a key goal of all healthcare interventions, including those for T2D management [ 12 ]. Furthermore, numerous studies have evaluated the QoL of people living with diabetes across numerous regions, including the United States [ 13 ], Europe [ 14 ], Asia [ 15 , 16 , 17 ], and Africa [ 18 , 19 ]. They have identified several associated factors, such as sex, age, financial status, educational attainment, occupations, body mass index (BMI), concomitant risk factors (dyslipidemia and hypertension), treatment therapy, and lifestyle [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerous studies have evaluated the QoL of people living with diabetes across numerous regions, including the United States [ 13 ], Europe [ 14 ], Asia [ 15 , 16 , 17 ], and Africa [ 18 , 19 ]. They have identified several associated factors, such as sex, age, financial status, educational attainment, occupations, body mass index (BMI), concomitant risk factors (dyslipidemia and hypertension), treatment therapy, and lifestyle [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Self-care behaviors (SCBs) are another factor that affects patient QoL [ 20 , 21 ], and Jeihooni et al suggested that a better QoL could be achieved by providing health education tailored to the needs of SCBs in patients with diabetes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of studies supported their claims with direct quotes from participants, it is important to note that the study conducted by de-Graft Aikins 33 did not provide such direct quotes after individual claims. The quantitative studies, on the other hand, were only lacking in either the use of non-validated measuring instruments for outcome assessment 27 or inadequate reporting of non-response bias. Details of the quality assessment are provided in Appendix 2.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of T2DM stigma ranged from 49.6% in Ghana 26 to 70% in Ethiopia. 27 Notably, younger adults tended to experience higher levels of diabetes stigma compared with older adults. 26 The presence of diabetes stigma was found to be associated with a lower quality of life among individuals with diabetes.…”
Section: Resultsmentioning
confidence: 99%